RELATIONSHIP BETWEEN WORK MOTIVATION AND JOB SATISFACTION OF SECONDARY SCHOOL TEACHERS - Salih Numan Zaheer; Dr. Muhammad Naveed Jabbar; Bushra Naheed (International Journal of Contemporary Issues in Social Sciences, 2024)
In the modern era, it has been examined that the leaders motivate their employees for attainment of maximum performance for development of organizations. The major aim of this research was to determine the relationship between work motivation and job satisfaction of the secondary school teacher. The public secondary school teachers from Gujranwala were administered as population of this study whereas, 263 respondents were selected as sample through simple random sampling technique. The structured questionnaires were administered for the collection of primary data through survey method. For data analysis the Statistical Package for Social Science (SPSS) was used according to the research objectives which were proposed in this study. The findings of the study indicated that work motivation plays a vital role for the enhancement of satisfaction level of the employees for the completion of organizational objectives successfully. Moreover, it was found that there was a significant relationship between work motivation with job satisfaction among secondary school teachers. This study is beneficial to adopt the new managerial strategies and techniques for the development of secondary education.